Description of Lysinibacillus telephonicus sp nov., isolated from the screen of a cellular phone - Rahi, Praveen; Kurli, Rashmi; Khairnar, Mitesh; Jagtap, Shubhangi; Pansare, Aabeejjeet N.; Dastager, Syed G.; Shouche, Yogesh S. (International Journal of Systematic and Evolutionary Microbiology, 2017)
A novel bacterial strain, designate dS5H2222(T), was isolated form the screen of a cellular phone. The cells were Gram-stainpositive, rod-shaped, aerobic and motile, and endospores are formed. S5H2222(T) grew as pale white colonies on trypticase soy agar and the best growth was observed at 37 degrees C (10- 55 degrees C) and at pH 7.0 (5.0-9.0). S5H2222(T) could tolerate up to 10% (w/v) NaCl. Phylogenetic analysis based on 16S rRNA gene sequences placed this strain within the genus Lysinibacillus and it exhibited high 16S rRNA gene sequence similarity to Lysinibacillus halotolerans LAM612(T) (97.8 %), Lysinibacillus chungkukjangi2RL3-2(T) (97.4 %) and Lysinibacillus sinduriensis BLB-1(T) (97.2 %). TheDNA- DNA relatedness of the strain with L. halotolerans JCM 19611(T), L. chungkukjangi KACC 16626(T) and L. sinduriensis KACC 16611(T) was 57, 64 and 55% respectively. The genomic DNA G+C content was 39.8 mol%. The major fatty acids of S5H2222(T) were iso-C-15:0, anteiso-C-15:0, iso-C-16:0 and anteiso-C-17:0. MK-7 was the only menaquinone and the main polar lipids were diphosphatidylglycerol, phosphatidylglycerol and phosphatidylethanolamine, four unidentified polar lipids were also present. The diagnostic amino acids in the cell wall peptidoglycan contained Lys-Asp (type A4 alpha). On the basis of the results of the phenotypic and genotypic characterizations, it was concluded that S5H2222(T) represents a novel species of the genus Lysinibacillus, for which the name Lysinibacillus telephonicus sp. nov. is proposed. The type strain is S5H2222(T) (=MCC 3065 T =KACC 18714(T)=LMG 29294(T)).